Does the municipal financial system promote a traffic-intensive settlement development of the city regions? - Gutsche, Jens-Martin (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
The article reviews the assumption that the German fiscal system has a traffic-generating effect by animating the municipalities through a potential fiscal surplus to have housing development activities within their boundaries even if these are generating more motorised traffic than they would in other municipalities in the region. The study is based on a household survey of traffic behaviour, on an analysis of regional house building rates and on a fiscal impact analysis. The results show that the signals sent out by the fiscal system towards municipal zoning policies are not in direct contradiction with the planning goal of a traffic-avoiding spatial structure. In fact their guiding effects are not strong enough to prevent a traffic-intensive sprawl in urban regions.